2013
DOI: 10.1080/19440049.2013.801088
|View full text |Cite
|
Sign up to set email alerts
|

Multi-residue method for the analysis of pesticides in Arabica coffee using liquid chromatography/tandem mass spectrometry

Abstract: Coffee is a major tropical agricultural commodity and represents a significant fraction of the economy of many countries. However, certain plant and animal species can damage coffee crops, affecting trade. A solution to this issue is the use of pesticides, some of which are harmful to human health and the environment. This work consisted of the development of a multi-residue method for the analysis of pesticides in coffee by using LC-MS/MS. The QuEChERS extraction procedure was used. The following analytical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…In previous reports, pymetrozine residues could be extracted from samples using acetonitrile (Dias et al, ; Jang et al, ; Zhang et al, ). For example, Jang et al found that methyl cyanide (MeCN) is a better exaction solvent for pymetrozine in pepper than ethyl acetate (EtOAc).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous reports, pymetrozine residues could be extracted from samples using acetonitrile (Dias et al, ; Jang et al, ; Zhang et al, ). For example, Jang et al found that methyl cyanide (MeCN) is a better exaction solvent for pymetrozine in pepper than ethyl acetate (EtOAc).…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports, pymetrozine residues could be extracted from samples using acetonitrile (Dias et al, 2013;Jang et al, 2014;Zhang et al, 2015). Garrido-Frenich, 2016; Walorczyk & Drożdżynski, 2012).…”
Section: Extraction and Purificationmentioning
confidence: 99%
See 3 more Smart Citations